Payload hardware and experimental protocol development to enable future testing of the effect of space microgravity on the resistance to gentamicin of uropathogenic Escherichia coli and its σs-deficient mutant. (November 2017) - Matin, A.C.; Wang, J.-H.; Keyhan, Mimi; Singh, Rachna; Benoit, Michael; Parra, Macarena P.; Padgen, Michael R.; Ricco, Antonio J.; Chin, Matthew; Friedericks, Charlie R.; Chinn, Tori N.; Cohen, Aaron; et al.
Highlights: A new, broadly applicable system for determining bacterial drug resistance in space. Potential measures to improve the management of urinary tract infections that can afflict astronauts. Determining if bacteria respond to microgravity as a stress akin to other insults. Abstract: Human immune response is compromised and bacteria can become more antibiotic resistant in space microgravity (MG). We report that under low-shear modeled microgravity (LSMMG), stationary-phase uropathogenic Escherichia coli (UPEC) become more resistant to gentamicin (Gm), and that this increase is dependent on the presence of σ s (a transcription regulator encoded by the rpoS gene). UPEC causes urinary tract infections (UTIs), reported to afflict astronauts; Gm is a standard treatment, so these findings could impact astronaut health. Because LSMMG findings can differ from MG, we report preparations to examine UPEC's Gm sensitivity during spaceflight using the E. coli Anti-Microbial Satellite ( EcAMSat ) as a free-flying "nanosatellite" in low Earth orbit. Within EcAMSat's payload, a 48-microwell fluidic card contains and supports study of bacterial cultures at constant temperature; optical absorbance changes in cell suspensions are made at three wavelengths for each microwell and a fluid-delivery system provides growth medium and predefined Gm concentrations. Performance characterization is reported here for spaceflight prototypes of this payload system. Using conventional microtiter plates, we show that Alamar Blue (AB) absorbance changes can assess the Gm effect on E. coli viability, permitting telemetric transfer of the spaceflight data to Earth. Laboratory results using payload prototypes are consistent with wellplate and flask findings of differential sensitivity of UPEC and its ∆ rpoS strain to Gm. if σ s plays the same role in space MG as in LSMMG and Earth gravity, countermeasures discovered in recent Earth studies (aimed at weakening the UPEC antioxidant defense) to control UPEC infections would prove useful also in space flights. Further, EcAMSat results should clarify inconsistencies from previous space experiments on bacterial antibiotic sensitivity and other issues.